Еще раз о термине гностик. II [Alexander Khosroyev: Further Remarks on the Term ‘Gnostic’. II] - Хосроев, А. Л. (Hyperboreus, 2026)
The paper collects and analyses main evidence on the use of the word γνωστικός in the 2nd–4th century philosophy, both pagan (Celsus, Plotinus, Porphyrius) and Christian heresiological (Irenaeus, Clemens, Hippolytus, Tertullianus, Epiphanius). Originally, Plato uses γνωστικός as an adjective (Polit. 258 E; γνωστικὴ ἐπιστήμη). In the second half of the 2nd century, followers of one of the early Christian opposition movements use the word as a self-epithet (e. g. Adv. haer. I. 11. 5: γνωστικῶν γνωστικώτεροι). Later the γνωστικός is substantivated, most likely under the influence of the Pauline Epistles (e. g. 1Cor 2. 14–16). Starting from Irenaeus, the word refers to any Christian dualist heretic.